Factors Influencing Entrepreneurial Motivation: A Case Study on a Beauty Store in Lhokseumawe City - Yusnaidah, Yusnaidah; Samsidar, Samsidar; agustinawati, Agustinawati; Terfiadi, Sari Yulis (Management Research and Behavior Journal, 2024)
This study aims to find out and analyze the Factors that Affect Entrepreneurial Motivation (Case Study on a Beauty Shop in Lhokseumawe City). The number of respondents used in this study amounted to 100 respondents. The method used to analyze the relationship between variables is the multiple linear regression analysis analysis method. The results of the study show that partially  the independence factor has a positive and significant effect on  entrepreneurial motivation in  Beauty Shops in Lhokseumawe City, Partially  the independence factor has a positive and significant effect on  entrepreneurial motivation in  Beauty Shops in Lhokseumawe City,  the Emotional factor has a positive and significant effect on Entrepreneurial Motivation in  Beauty Stores in Lhokseumawe City, Independence Factor Has a Positive and Significant Effect on Entrepreneurial Motivation in Beauty Stores in Lhokseumawe City.